SOLID FUEL FROM EMPTY FRUIT BUNCH FIBER AND WASTE PAPERS PART 3: ASH CONTENT FROM COMBUSTION TEST - YAAKOB, MOHD YUHAZRI; HASOLOAN, HAERY IAN PIETER; YAHAYA, SAIFUDIN HAFIZ; SAID, MD RADZAI (Global Engineers and Technologists Review, 2012)
This research discussed on the results obtained for each sample that have been conducted to the solid fuel briquettes made of empty fruit bunch fiber and waste papers from view of ash content during combustion test. The results shows tremendous amount of ash content can be generated from these biomass compositions. Percentage of ash content in every composition is important to know how much ash produced every burning process because this is really related to environmental issues (human and equipment, i.e hygiene). Hence, the possibility result in this research is the development of solid fuel briquette by mixing the empty fruit bunch with a waste paper can be one sources of fuel energy. From the combustion analysis shows sample briquette of S/N 5 was found to be the best ratio as the amount of ash produced at the end of combustion process is the least compared to others researcher with a value of 1.11 percent.